THE CONCEPT OF COMPETITION AND ITS MANIFESTATION IN DIGITAL JOURNALISM - Sultanova, Sayyora Ulugbekovna; Ikramova , S.A. (Educational Research in Universal Sciences, 2023)
This article talks about the concept of competition, its uniqueness and the concept, place and manifestations of competition in digital journalism.